AVANÇO DO CONSERVADORISMO NO BRASIL: a PEC nº. 181/2015 e o regresso na legislação permissiva do aborto - Maricy Ribeiro Fideles Rocha (Universidade Federal do Maranhão, 2018)
The present work aims to throw a critical view on conservatism in Brazil, es- pecially regarding the issue of abortion. In order to do so, it conceptualizes abortion and exposes the preliminaries of the theme, listing data on abortion practice in Brazil, Latin America and the World, later characterizing conser- vatism as a category, relating recent Ibope Intelligence research on the level of Brazilian conservatism. Finally, it analyzes the Proposal of Constitutional Amendment nº. 181/2015, called PEC Trojan Horse, especially with respect to its content that, using conservative ideals, hardens the permissive legislation of abortive practice. It uses bibliographical research, aiming to cover the largest number of positions on the subject.